Proceso de atención de enfermería de paciente de 25 semanas de gestación con oligohidramnio y anemia en el Hospital Materno Infantil Dra. Matilde Hidalgo de Procel - Montoya Mora, Ginger Andreina (2020)
The nursing care process is the application of the scientific method that allows health professionals to provide care that the patient needs in a structured, logical way based on very structured protocols. Oligohydramnio is a disorder that is often associated with complications in both fetal integrity and in the state of maternal health; Its definition implies a decrease in the amount of amniotic fluid, but its diagnosis depends on the criteria used to assess the amount of fluid. The objective of this clinical case is to apply the nursing care process to a 25-week-old pregnant woman with oligohydramnio and hospitalized anemia at the Maternal and Child Hospital Dr. Matilde hidalgo de Procel. Anemia is one of the most frequent complications during pregnancy (suffered by up to 95% of pregnant women) and is caused by a decrease in iron below normal values.